SIFAT FISIS PAPAN GYPSUM DARI LIMBAH GERGAJIAN KAYU - Saibatul Hamdi (Jurnal Riset Industri Hasil Hutan, 2013)
The purpose of this research is to exploit the waste ripsaw  as substitution of gypsum board on the fhysical of board gypsum. Raw material in the form of waste saw from particle of wood kambang (Goniothalamus Sp), wood tarap (Artocarpus Elasticus REINW) and wood lua  (Ficus Glomerata ROXB) size of particle 40 mesh and 60 mesh, while preservative use the ammonium of concentration borax 1% and 2% percentage gypsum to ripsaw particle 300, 400 and 500%. Research result show the rate mean irrigate to range from 10,02-14,61%, closeness 0,72-0,98 g/cm3, absorpsion irrigate 19,98-28,15%, thick development 0,95-1,93% and linear development 0,12-0,60%. As a whole examination of nature of fisis of board gypsum fulfill the standard of quality of board of gypsum SNI 03-6434-2000 except to rate examination irrigate and linear development not fulfilled the standard quality of gypsum board. Pursuant to this research result can be considered by industry gypsum to exploit the waste saw as substitution in making of board gypsum to be improve repairing the nature of rate irrigate and linear development.Keyword : waste powder ripsaw, lua, kambang, tarap, gypsum